(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In given article the issues of migration are considered and the approaches to solve these issues have been offered. Also, regularities and features of internal migration are defi ned. Authors recommend the approaches to facilitate the conditions of migrators. The reasons and main tendencies of internal and external migration of Republic of Kazakhstan are analyzed. The issues of migration from countries to the cities are analyzed. Keywords: migration, internal migration, urbanization, international migration